2013
DOI: 10.4028/www.scientific.net/amr.687.204
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Polymer Modified Concrete in Fresh and Hardened State

Abstract: It was carried out a study on the properties of polymer modified concrete (PCM) in fresh and hardened state. It was used three types of polymers: epoxy resins, polyurethane and methylcellulose in different percentages and different water cement ratio.The main objectives was to improve workability and rheological behavior of these mixtures in fresh state and mechanical strength tests on hard concrete. Has been investigated the polymer influence on compression strength and flexural strength and analyzing the tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Several papers, due to the research leitmotiv or due to the level of consideration, could be treated as 'trailers' of nanotechnology in C-PC [e.g. [22][23][24][25]. It is a universal paradox, which if the system is more complicated the more powerful function belongs to the smaller player.…”
Section: Research Areamentioning
confidence: 99%
“…Several papers, due to the research leitmotiv or due to the level of consideration, could be treated as 'trailers' of nanotechnology in C-PC [e.g. [22][23][24][25]. It is a universal paradox, which if the system is more complicated the more powerful function belongs to the smaller player.…”
Section: Research Areamentioning
confidence: 99%
“…Ariffin et al (2018) showed that the use of 5% liquid latex polymer increased the concrete compressive strength up to 133.3%. Ion et al (2013) investigated whether the use of epoxy resin could result in a higher influence on the workability of the resulting concrete than the use of other types. The slump of concrete matrix having 10% epoxy resin was about 67 mm whereas those of concrete matrices having 10% polyurethane and 0.6% methylcellulose were 7 and 58 mm, respectively.…”
Section: Introductionmentioning
confidence: 99%